Whistle-Blowing for Profit: An Ethical Analysis of the Federal False Claims Act - Carson, Thomas L. (Journal of business ethics, 2007)
This paper focuses on the 1986 Amendments to the False Claims Act of 1863, which offers whistle-blowers financial rewards for disclosing fraud committed against the U.S. government. This law provides an opportunity to examine underlying assumptions about the morality of whistle-blowing and to consider the merits of increased reliance on whistle-blowing to protect the public interest. The law seems open to a number of moral objections, most notably that it exerts a morally corrupting influence on whistle-blowers. We answer these objections and argue that the law is not objectionable on these grounds. Since there are no compelling moral objections to the law, it is appropriate and acceptable to judge the law in terms of its economic costs and benefits. We assess the most salient of these and conclude that the benefits outweigh the costs. We suggest that a mechanism similar to the Act should be considered for protecting stockholders’ interests in the private sector. We conclude by making several proposals for improving the existing legislation.